Guest

if z=f(x,y) where x=uv and y=u/v then show that (∂z/∂y)=(v-2)(∂z/∂u)-(v²/2u)(∂z/∂v)

if z=f(x,y) where x=uv and y=u/v then show that (∂z/∂y)=(v-2)(∂z/∂u)-(v²/2u)(∂z/∂v)

Grade:12th pass

1 Answers

Vikas TU
14149 Points
2 years ago
Dear student 
Please give the value of function , After that we can proove anything. ,,,,,,,,,,,,,,,,,,,
Good Luck 

Think You Can Provide A Better Answer ?

Provide a better Answer & Earn Cool Goodies See our forum point policy

ASK QUESTION

Get your questions answered by the expert for free